(untitled) (Research, Society and Development, 2021)
Purpose: To construct and validate a book on wound teaching, classification, assessment and treatment of wounds in order to make it a health educational technology to be used by students and health professionals. Methodology: This is a methodological development for validation of a wound book. The study sample consisted of expert judges, which was necessary in the validation process because of the importance of judging the specific and thematic content of the book. For quantitative data analysis, the calculation of the Content Validity Index (CVI) was performed and to evaluate the questionnaire used in this study, Cronbach’s alpha coefficient was used. Results: The instrument was considered validated by the judges, demonstrating desirable internal consistency with Cronbach’s alpha coefficient of 0.95 which is an important instrument when aiming to measure single construct through multiple items, and the book showed overall CVI of 0.99 with excellent level of agreement, it can be inferred that the tool is representative of the content to be addressed on nursing education in relation to the wound. Conclusion: the book is a valid educational technology to be used in the teaching of wound assessment and treatment in nursing education, in order to provide a meaningful and effective learning process for students.